2022
DOI: 10.1029/2022ja030676
|View full text |Cite
|
Sign up to set email alerts
|

The Dawn‐Dusk Tail Lobe Magnetotail Configuration and the Formation of Aurora Transpolar Arc

Abstract: Most of the disturbances in space environment can be explained under the framework theory of open magnetosphere and Dungey cycle (Dungey, 1961). This theory is sketched in Figure 1 which is similar to Dungey's original figure. Under southward IMF (SIMF) conditions, magnetic reconnection occurs first at the nose of the magnetopause (Figure 1c) where IMF field lines interconnect with dayside geomagnetic closed field lines. Such reconnection creates a northern set and a southern set of open field lines that conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(22 citation statements)
references
References 59 publications
10
12
0
Order By: Relevance
“…(2005) would be more consistent with the results of Li et al. (2021, 2022), which are in turn consistent with our results. Interestingly, very similar dawn–dusk open lobe populations and resulting closed wedge structures that form in the high latitudes are present in simulations using real events (such as those discussed by Li et al.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…(2005) would be more consistent with the results of Li et al. (2021, 2022), which are in turn consistent with our results. Interestingly, very similar dawn–dusk open lobe populations and resulting closed wedge structures that form in the high latitudes are present in simulations using real events (such as those discussed by Li et al.…”
Section: Discussionsupporting
confidence: 94%
“…It is not clear, from an observational point of view, how closely this resembles the real magnetosphere under northward IMF conditions (when the magnetotail's structure will be influenced by earlier periods of southward IMF and the pre-existing high-latitude field lines are open). However, we note that the structure in Figure 1a resembles that expected for reconnection with initially closed high-latitude field lines (Cowley, 1981(Cowley, , 1983Crooker, 1992;Fuselier et al, 2015;Milan et al, 2022) and also that observed in other simulations that are initialized with northward IMF conditions (e.g., Li et al, 2021Li et al, , 2022.…”
Section: Comparison With Kullen and Janhunen (2004)supporting
confidence: 77%
See 3 more Smart Citations